Testing a Model to Explain how the Public Makes Decisions about Genetic Modification - Alexa J. Lamm; Kevan W. Lamm; Joy N. Rumble; Jason D. Ellis; Abraham Tidwell (Journal of International Agricultural and Extension Education, 2020)
The international agricultural and extension education field is fairly infantile in its research approach with descriptive, exploratory and process-oriented research taking the forefront over the introduction and testing of theoretical models that strive to answer complex questions. In a time when the world is facing a myriad of global challenges directly related to the agricultural and natural resource system (e.g. food security, climate change, infectious disease management) the discipline must be bold, innovative, and discovery-driven. The research presented here tests a theoretical model that combines two well-known theories, Diffusion of Innovations and Spiral of Silence, in the context of examining public willingness to expose attitudes about genetic modification (GM) in the United States. Structural equation modeling is used to determine the direct and indirect effects theoretical variables can have in a complex decision-making environment. Perceptions of diffusion characteristics of an innovation were found to directly and indirectly effect perceived opinions of others, perceived future trends in attitudes toward GM, and attitude toward GM but they did not have a significant direct or indirect effect on willingness to expose attitudes about GM. The findings revealed the ongoing complexity associated with systems-thinking and the research approaches necessary to answer complex questions. It also showcased that when thoroughly vetted theoretical explanations are tested, they will not always have the expected result
Keywords: systems thinking; decision-making; diffusion; spiral of silence